2006
DOI: 10.1002/jat.1129
|View full text |Cite
|
Sign up to set email alerts
|

Hematological parameters in tenchTinca tinca after short term exposure to lead

Abstract: Alterations in the hematological parameters of Tinca tinca were studied after exposure to lead at different concentrations and durations of exposure. Dose of 75/24 (ppm/h) did not cause significant change in any blood parameter. The 300/48 dose caused a significant increase in hematocrit (Hct), mean corpuscular volume (MCV) and mean corpuscular hemoglobin (MCH) and a significant decrease in red blood cell (RBC) count and mean corpuscular hemoglobin concentration (MCHC). The 30/24 dose caused a significant incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 26 publications
8
40
0
2
Order By: Relevance
“…In the present study, the significant increase in WBC count indicate hypersensitivity of these cells to dried poultry droppings and the changes may be due to immunological reaction to produce more antibodies to combat the stress induced through exposure to the dried poultry wastes. The significant increase (p<0.05) observed for MCV and MCH in test fish T5 compared to the control may be attributed to direct or feedback responses of structural damage to red blood cell membranes resulting in haemolysis and impairment in haemoglobin synthesis and stress-related release of red blood cells from the spleen and hypoxia, induced by exposure to toxicant (Shah, 2006).…”
Section: Resultsmentioning
confidence: 93%
“…In the present study, the significant increase in WBC count indicate hypersensitivity of these cells to dried poultry droppings and the changes may be due to immunological reaction to produce more antibodies to combat the stress induced through exposure to the dried poultry wastes. The significant increase (p<0.05) observed for MCV and MCH in test fish T5 compared to the control may be attributed to direct or feedback responses of structural damage to red blood cell membranes resulting in haemolysis and impairment in haemoglobin synthesis and stress-related release of red blood cells from the spleen and hypoxia, induced by exposure to toxicant (Shah, 2006).…”
Section: Resultsmentioning
confidence: 93%
“…Fish exposed to metals, pesticides and effluents exhibit hematological changes, not only after laboratory exposure, but also when the exposure occurs in the field (RANZANI-PAIVA et al, 1997;OLIVEIRA-RIBEIRO et al, 2006;ADHIKARI, 2004;SHAH, 2006;FRANÇA et al, 2007). Other authors reported that such responses may vary according to the gender, as observed for Salminus maxilosus (RANZANI-PAIVA et al, 2003).…”
Section: Discusssionmentioning
confidence: 99%
“…An alternative hypothesis, in which the erythrocytes have suffered haemolysis (SHAH, 2006, ADHIKARI et al, 2004, FRANÇA et al, 2007, can be discarded, since the SES fish exhibited high levels of MCHC and Hb. Only the reduction of Er does not necessarily indicate hemolysis because, in this case, there is also a reduction of Hb by leaching, reducing its erythrocyte concentration (MCHC).…”
Section: Discusssionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in MCV, MCH and MCHC is in agreement with the work of Ariweriokuma et al (2011) following a shoot term exposure of C. gariepinus to cypermethrin in the laboratory. These alterations were attributed to direct or feedback response of structural impairment to RBC membranes resulting in haemolysis and impairment in haemoglobin producyion, stress-related release of RBCS from the spleen and hypoxia stimulated by exposure to atrazine and metolachlor (Shah, 2006;Akinrotimi and Gabriel, 2012b).…”
Section: Journal Of Fisheriessciencescom George Adi Et Al 11(3): 0mentioning
confidence: 99%